Chemotherapy and Immune Checkpoint Inhibitors in a Case of SMARCA4-dUT: A Case Report and Review of Literature - Akriti Pokhrel MD; Ruchi Yadav MD; Kapil Kumar Manvar MD; Richard Wu MD; Vijay Jaswani MD; Carrie Brooke Wasserman MD; Jen C. Wang MD (SAGE Publishing, 2023)
SMARCA4-deficient undifferentiated tumors (SMARCA4-dUT) are infrequently occurring aggressive neoplasms found predominantly in young male smokers. These tumors are distinguished by the loss of expression of Brahma-related gene 1 (BRG1) due to a deactivating mutation of SMARCA4. Immunophenotype can be variable but characteristically lack the expression of BRG1. SMARCA4-dUT has a poor prognosis and generally progresses or recurs. The median survival is around 6 months. Here, we report a case of a 36-year-old male smoker who presents with multiple right-sided lung masses. The patient was found to have a loss of SMARAC4 and SMARCA2 along with the absence of markers of vascular, melanocytic, lymphoid, keratin, or myogenic origin. Tumor size was reduced significantly after 3 cycles of carboplatin and 1 cycle of pembrolizumab. From reviewing the literature and the clinical course in our case, we suggest combination chemotherapy plus immune checkpoint inhibitor (ICI) therapy to be the first choice of therapy for treating SMARCA4-dUT of lungs. Further research and studies are needed to evaluate the response to ICI therapy alone or combination therapy (chemotherapy plus ICI).